Exploring the role of hypercholesterolemia in tendon health and repair - Hast, Michael W. (Muscles Ligaments Tendons J, 2014)
High cholesterol remains a significant healthcare problem, as more than 13% of adults in the U.S. are affected by hypercholesterolemia. The detrimental effects the disease has on cardiovascular health are well-documented, but the effects on the musculoskeletal system, and more specifically on tendons, have not been thoroughly examined. This paper provides an overview of work performed in our lab with various animal models to elucidate the relationship between high cholesterol and tendon biomechanical integrity and ability to heal. These studies highlight the complexity of relationships between multiple factors that influence tendon biomechanics, and it has offered a better understanding of the implications of high cholesterol on healthy and healing tendons.